Harnessing Hydropower Potential in Desert Regions: The Case of Wadi Dayqah Dam, Quriyat, Oman - Okedu, Kenneth E.; Al Siyabi, Mohsin Said (Frontiers in Water, 2021)
Hydropower technology is a simple and renewable form of energy that involves the conversion of potential energy due to head and mass flow rate of water, into kinetic energy that drives a water turbine connected to a generator. In this paper, the potential of hydropower in the Sultanate of Oman is studied, considering wadi Dayqah dam in Quriyat. The following variables of the dam were used in evaluating its potential for electricity generation for the year 2010 through 2018; the amount of water flowing in and out of the dam, the amount of water available in the dam at the beginning and end of the considered years. Recommendation was made for the type of hydro turbine for maximum power extraction from the dam, based on the available water head and flow rate, considering the standard characteristics selection envelope for hydro turbines. Power generation from the dam could be affected as a result of the decline in reservoir water level, by the continuous release of water for irrigation purposes, fear of the aftermath of cyclone, lack of rains for consecutive years and high evaporation. However, the occurrence of cyclone, increases the reservoir water level of the dam for more power generation.